PSYCHOLOGICAL READINESS OF SECONDARY VOCATIONAL EDUCATION TEACHERS FOR MASTERING NEW ACTIVITIES IN THE CONTEXT OF PROFESSIONAL REORIENTATION - I. I. Khasanova; S. S. Kotova (Образование и наука)
Introduction. In the context of fundamental changes which have occurred in the last decades in the world of professions and transition from monoprofessionalism to poly-professionalism, a modern man needs to have an ability to freely navigate the modern labour market, to quickly diversify contents and quality of the professional activity, and, if thought appropriate, to change an occupation without difficulty. Nowadays, the requirements for the teachers of vocational training are designed in a completely different way to provide high-quality lifelong learning.The aim of the research is to reveal the psychological readiness of teachers of vocational school for the development of new types of learning activities in the conditions of a professional reorientation.Methodology and research methods. The methodological framework of the present research is based on conceptual provisions of the personal-focused, subject, competency-based and system approaches to vocational education, as well as theories of the psychology of abilities and organization of continuing the professional education of adults. General scientific methods such as analysis, synthesis, specification and generalization were applied. Techniques of psychological and pedagogical observation and questionnaire were used at the diagnostic phase of the study as the leading ones.Results and scientific novelty. The concepts of “professionalization”, “professional self-determination”, “transprofessional competencies” and “psycho-pedagogical assistance” are clarified. It is stated that under the increasingly complex socio-cultural and professional environment there is the need for pedagogical personnel capable to carry out continuing training and retraining of mid-level professionals for the real sector of the economy and the social sphere in compliance with the international standards and advanced technologies. Based on the content of scientific sources, a list of systematically important transprofessional competencies to provide psychological readiness of teachers of vocational school for new kinds of activities is drawn up. Results of a diagnostic questioning are described; the respondents were teachers and employees of methodical offices of vocational-oriented education of various colleges of Yekaterinburg and Novouralsk who do not have a basic pedagogical education. Using the processing of the obtained data, it is established that teachers, on the one hand, understand the essence and objectives of their work; on the other, they can not independently respond to their personal needs to reevaluate own professional position due to the use of outdated methods and stereotypic ways of training. Conclusions are drawn that most of the interviewed teachers have no ability to conduct overtime professional activity that enables to carry a standard teaching load; a considerable part of teachers need acquisition of additional pedagogical and transprofessional competencies.The authors outlined the proposal to develop a combinatory technology of psycho-pedagogical support for teachers of vocational schools to improve the current situation. The functionality of this technology, its tasks, structural components, possible methods and estimated effects of its implementation in practice of the SPE (Secondary Professional Education) system are noted.Practical significance. The materials of the present paper can be useful for managerial staff, psychologists and training specialists of the SPE system who are engaged in the issues of teacher professional development.